Beyond the roof of the world music, prayer, and healing in the Pamir mountains - Koen, Benjamin D.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2009)
This work demonstrates the relevance of medical ethnomusicology in light of the globally spreading ICAM (integrative complementary, and alternative medicine) approaches to health and healing.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Healing -- Pamir-Alain Mountains Region; Spiritual healing -- Pamir-Alain Mountains Region; Holistic medicine -- Pamir-Alain Mountains Region; Music therapy -- Pamir-Alain Mountains Region; Prayer -- Pamir-Alain Mountains Region; Electronic books